Health Behavior pada Pasien HIV AIDS di Kota Salatiga - Desi, Desi; Lase, Priskila; Anwar, Muh Aziz (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Healthy behavior is a person's reaction to improve, fight for, maintain his health. Healthy behavior is related to individual actions such as exercise, rest, fulfillment of nutritional needs, personal care and hygiene, as well as cleanliness of reproductive organs and use of condoms for people living with HIV/AIDS (ODHA) so that they are not transmitted to others, so it is important to implement life behaviors healthy. The Salatiga City Health Office explained that in 2017 the number of HIV/AIDS sufferers reached 250, in 2018 there were 271 people, in 2019 there were 285 people who were infected by July 2020 there were 300 cases of HIV/AIDS. This study aims to determine the description of healthy behavior in HIV/AIDS sufferers in the City of Salatiga.Methods is qualitative research with a case study approach. Respondents in this study were 4 people infected with HIV/AIDS. It was held from September to November 2020. Data was collected by means of in depth interviews and using interview guide sheets.Results Healthy behavior carried out by ODHA to maintain and strive for their health is by doing physical activity and useful sports, healthy and nutritious nutrition, maintaining personal hygiene and reproductive hygiene, providing and using condoms when engaging in sexual activity, adhering to taking ARVs, and groups. peer support (KDS) which has a good influence on awareness of the healthy life of HIV/AIDS patients in Salatiga City.Conclusion Healthy behavior has an important role in the condition of PLWHA in Salatiga which is able to make ODHA more confident and productive.